Identification of Protein Coding Regions in the Human Genome by Quadratic Discriminant Analysis - Zhang, M. Q. (Proceedings of the National Academy of Sciences - PNAS, 1997)
A new method for predicting internal coding exons in genomic DNA sequences has been developed. This method is based on a prediction algorithm that uses the quadratic discriminant function for multivariate statistical pattern recognition. Substantial improvements have been made (with only 9 discriminant variables) when compared with existing methods: HEXON [Solovyev, V. V., Salamov, A. A. & Lawrence, C. B. (1994) Nucleic Acids Res. 22, 5156-5163] (based on linear discriminant analysis) and GRAIL2 [Uberbacher, E. C. & Mural, R. J. (1991) Proc. Natl. Acad. Sci. USA 88, 11261-11265] (based on neural networks). A computer program called MZEF is freely available to the genome community and allows users to adjust prior probability and to output alternative overlapping exons.